1971
DOI: 10.1111/j.1432-1033.1971.tb01620.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of the Crystalline Inclusion of Bacillus thuringiensis during Sporulation

Abstract: The biogenesis of the crystalline inclusion of Bacillus thuringiensis has been studied in the more general context of sporulation and in regard to the formation of some spore constituents.It has been shown that crystal protein is essentially formed during stages TI1 and IV, before the acquisition of octanol resistance. One fraction of protein spore coats which is solubilized by a reducing agent associated with urea or guanidine hydrochloride, is synthesised a t the same time ; a more insoluble cystine-rich fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 27 publications
0
31
0
1
Order By: Relevance
“…The intracellular protein crystals produced by sporulating cells of Bacillus thuringiensis account for 20-30% of the dry weight of sporulated cultures (1)(2)(3). The crystals are composed of repeating subunits of a Mr 130,000 polypeptide (4,5) which is thought also to be a major component ofthe spore coat ofcrystalproducing strains (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular protein crystals produced by sporulating cells of Bacillus thuringiensis account for 20-30% of the dry weight of sporulated cultures (1)(2)(3). The crystals are composed of repeating subunits of a Mr 130,000 polypeptide (4,5) which is thought also to be a major component ofthe spore coat ofcrystalproducing strains (6,7).…”
mentioning
confidence: 99%
“…When the large plasmid fraction was used as a source of inserts, one colony was found that reacted specifically with antibodies to the 1 Fig. 1) (39).…”
mentioning
confidence: 99%
“…After 72 h, one fraction of bacterial suspension was centrifuged at 8500 g for 15 min, the culture supernatants were collected. The spore crystal mixtures were prepared according to Lecadet and Dedonder (1971).…”
Section: Methodsmentioning
confidence: 99%
“…Considerable evidence has accumulated (see above, and Lecadet & Dedonder, 1971 ;Ribier, 1971;Lecadet, Chevrier & Dedonder, 1972;Ribier & Lecadet, 1973;Herbert & Gould, 1973) indicating a relationship between the protein of the crystal of B. thuringiensis and spore material which is solubilized under conditions similar to those necessary to dissolve crystals. However, the toxicity of spore extracts has not previously been reported although whole spores are known to be toxic.…”
Section: Discussionmentioning
confidence: 99%